SISTEM PENDUKUNG KEPUTUSAN PEMILIHAN TOKO HANDPHONE TERBAIK DI KOTA PADANGSIDIMPUAN MENGGUNAKAN METODE ORESTE - Aldo, Dasril; Alwendi, Alwendi (Sekolah Tinggi Manajemen Informatika dan Komputer GICI, 2020)
This research will discuss about the selection of the best mobile shops in the city of Padangsidimpuan. This research was conducted to find out the best mobile shop in the city of Padangsidimpuangiven to consumers through a Questionnaire. This study uses a Decision Support System with the Oreste method. The Oreste Method is one of the Decision Support System methods supported by Besson Ranking, which is the priority scale of each criterion indicator. The data used as an alternative is the data of cellphone shops in Padangsidimpuanwith a sample of 5 stores with 5 criteria, namely Price, Quality on Cellphones, Services, Consumer Attraction and Store Locations. The mount phase that is carried out in selecting a cell phone shop starts with analyzing the system that is done at the cellphone shop, then from the results of the analysis carried out weighting criteria at the cellphone shop, then carried out alternative weighting at the cell phone shop. After that the process of ranking the weight of alternative handphone shops is carried out. Based on alternative data and criteria using the Oreste method, it can be concluded that the best mobile shop is the Happy Cellular Shop with a Preference Value of Distance Score Value of 5.3556. Smaller than the other 4 stores.